Examination of Kutadgu Bilig in Terms of Values - Uçar, Emel; Karasu Avcı, Emine (Degerler Egitimi Dergisi, 2025)
Kutadgu Bilig, written by Yusuf Has Hacip in 1070, is a didactic and advisory work. The title of the work means “Knowledge That Brings Happiness,” and it examines the relationship between individuals and state governance while also shedding light on the moral and social values of society. Kutadgu Bilig is not only relevant to the pe-riod in which it was written but also serves as a guide for modern readers, addressing the connections between individuals, society, and the state. This study aims to identify the values contained in the work and determine how these values are represented. During data analysis, the content analysis method was applied. As a result of the research, a total of 24 different values were identified in Kutadgu Bilig. These values include justice, empha-sis on family unity, independence, peace, scientific thinking, generosity, diligence, solidarity, sensitivity, friends-hip, honesty, aesthetics, sacrifice, self-discipline, freedom, patience, respect, love, responsibility, frugality, sub-mission to fate, and patriotism. The most emphasized values in the work are justice and solidarity, while values such as patience, diligence, and frugality are less prominent. The study identified that these values are conveyed through couplets. In this respect, Kutadgu Bilig can be regarded as a significant source for values education.